The Importance of Intercultural Communication in Nursing (Journal of Universal Excellence, 2026)
Research Question (RQ): Intercultural communication is very important in dealing with patients from different cultures, but this is where misunderstandings often arise. In line with the subject and purpose of the survey, we have raised the following three research questions: To what extent are nurses sympathetic to the treatment of foreign-speaking patients? How much knowledge do nurses have about intercultural communication, which contributes to the quality of treatment of foreign-speaking patients? What are the most common barriers to treating foreign-speaking patients?Purpose: The aim of this study was to determine how nurses face with obstacles created by intercultural communication, what these obstacles are and whether the nurses are taught about intercultural communication.  Method: A qualitative descriptive methodology was used. We conducted two focus interviews, in each group participated four nurses from primary and secondary activities. We analyzed the data by a thematic analysis of the data.Results: We identified two topics: (1) characteristics of communication in nursing, (2) interculturalism in nursing. Nurses described intercultural communication as very important for understanding patient’s problems and needs. They have pointed out that they want additional education of intercultural communication, since knowledge to date is not sufficient. Language was most often cited as an obstacle to intercultural communication; however, they also help themselves through non-verbal communication and interpreters.Organization: A higher level of cultural competences among health professionals enables better health care for patients coming from other cultures. Additional intercultural education would help health professionals with the challenges of transcultural nursing.Society: Based on the findings, we demonstrated the lack of knowledge of nurses about intercultural communication. Therefore, we propose the implementation of additional training on intercultural communication for health professionals, which would have a positive impact on the more appropriate inclusion of patients from foreign cultures in health care.Originality: We have not found much research in the Slovenian literature on the topic of intercultural communication in nursing. With our research, we have proven that nurses have a lot of problems in the health care of patients from foreign cultures.Limitations/Future Research: The research was limited to nurses from the Gorizia region. In further research, it would be good to invite health professionals from different cultures to participate, so that they can compare their views on intercultural communication with the views of health professionals with Slovenian roots.
Keywords: transculture; conversation; culture; competence; nurse